Thousands of Novel Transcripts Identified in Mouse Cerebrum, Testis, and ES Cells Based on ribo-minus RNA Sequencing - Liu, Wanfei; Zhao, Yuhui; Cui, Peng; Lin, Qiang; Ding, Feng; Xin, Chengqi; Tan, Xinyu; Song, Shuhui; Yu, Jun; Hu, Songnian (Frontiers in Genetics, 2011)
The high-throughput next-generation sequencing technologies provide an excellent opportunity for the detection of less-abundance transcripts that may not be identifiable by previously-available techniques. Here, we report a discovery of thousands of novel transcripts (mostly non-coding RNAs) that are expressed in mouse cerebrum, testis, and embryonic stem (ES) cells, through in-depth analysis of rmRNA-seq data. These transcripts show significant associations with transcriptional start and elongation signals. At the upstream of these transcripts we observe significant enrichment of histone marks (histone H3 lysine 4 trimethylation, H3K4me3), RNAPII binding, and CAGE tags that marks transcriptional start sites. Along the length of these transcripts, we also observe enrichment of histone H3 lysine 36 trimethylation (H3K36me3). Moreover, these transcripts show strong purifying selection in their genomic loci, exonic sequences, and promoter regions, implying functional constraints on the evolution of these transcripts. These results define a collection of novel transcripts in the mouse genome and indicate the potential function in the mouse tissues or cells.